Superhero Joe - Weitzman, Jacqueline Preiss; Barrett, Ron (New York : Simon & Schuster Books for Young Readers, 2011)
Five-year-old Joey uses his super powers to help his parents out of a sticky situation.
"A Paula Wiseman Book."
School Library Journal
School Library Journal, August 2011
3.6
K-3
K-3
Keywords: Fear -- Juvenile fiction; Imagination -- Juvenile fiction; Superheroes -- Juvenile fiction; Cartoons and comics; Fear -- Fiction; Imagination -- Fiction; Superheroes -- Fiction; Comic books, strips, etc; Fear -- Fiction; Imagination -- Fiction; Superheroes -- Fiction; Picture books for children